Gut microbiota therapy in gastrointestinal diseases - Hanif Ullah; Safia Arbab; Chengting Chang; Saira Bibi; Nehaz Muhammad; Sajid Ur Rehman; Suleman; Suleman; Irfan Ullah; Inam Ul Hassan; Yali Tian; Ka Li (Frontiers in Cell and Developmental Biology)
The human gut microbiota, consisting of trillions of microorganisms, plays a crucial role in gastrointestinal (GI) health and disease. Dysbiosis, an imbalance in microbial composition, has been linked to a range of GI disorders, including inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), celiac disease, and colorectal cancer. These conditions are influenced by the interactions between the gut microbiota, the host immune system, and the gut-brain axis. Recent research has highlighted the potential for microbiome-based therapeutic strategies, such as probiotics, prebiotics, fecal microbiota transplantation (FMT), and dietary modifications, to restore microbial balance and alleviate disease symptoms. This review examines the role of gut microbiota in the pathogenesis of common gastrointestinal diseases and explores emerging therapeutic approaches aimed at modulating the microbiome. We discuss the scientific foundations of these interventions, their clinical effectiveness, and the challenges in their implementation. The review underscores the therapeutic potential of microbiome-targeted treatments as a novel approach to managing GI disorders, offering personalized and alternative options to conventional therapies. As research in this field continues to evolve, microbiome-based interventions hold promise for improving the treatment and prevention of gastrointestinal diseases.